Women's empowerment in rural Honduras and its determinants: insights from coffee communities in Ocotepeque and Copan. Issue 1 (2nd January 2018) - Dietz, Thomas; Estrella Chong, Andrea; Font Gilabert, Paulino; Grabs, Janina
ABSTRACT: This article quantifies the level of women's empowerment in western Honduran coffee-producing households through the construction of the Women's Empowerment in Agriculture Index, and highlights the determinants of each empowerment indicator and their interactions. Women in the study region suffer from a lack of control over use of income and access to productive resources. Since control and ownership of assets are positively correlated with input in productive decisions and control over the use of income in this study region, it is suggested that "low-hanging fruit" to improve empowerment would be to invest in interventions that strengthen asset control and distribution.